Asuhan Kebidanan Continuity Of Care (COC) pada Ny. A Umur 26 Tahun G1P0A0 di Wilayah Kerja Puskesmas Semowo - Sri Sulistyani; Kartika Sari (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Pregnancy, childbirth, the postpartum period, and the neonatal period are physiological processes that have the potential to pose risks to both the mother and the infant. An optimal effort to ensure maternal and neonatal safety is the implementation of Comprehensive Midwifery Care (Continuity of Care/COC). The COC care provided to Mrs. A aimed to deliver continuous and integrated midwifery services during pregnancy, childbirth, postpartum, newborn care, and family planning (FP) for a primigravida mother (G1P0A0). This study used a case study method with a descriptive design. The subject was a second-trimester pregnant woman at 29 weeks of gestation in the working area of Semowo Public Health Center. Data were collected through interviews, observations, physical examinations, SOAP documentation, and review of the Maternal and Child Health (MCH) handbook, using Varney’s midwifery management approach. The results showed that during pregnancy, Mrs. A experienced common discomforts in the second and third trimesters, such as fatigue and sleep disturbances. She received education on adequate rest, relaxation techniques, balanced nutrition, and danger signs of pregnancy. The childbirth process progressed normally, and the baby was born healthy with anthropometric measurements appropriate for gestational age, while initial screenings (CHT and OAE) showed normal results. During the postpartum period, Mrs. A experienced nipple soreness, for which breast care education and proper breastfeeding techniques were provided. During neonatal visits, the baby exhibited sleep disturbances, and baby massage was performed to improve sleep quality and bonding. In the family planning stage, Mrs. A chose the implant contraceptive method after receiving counseling, and the insertion was successfully completed.   Abstrak Masa kehamilan, persalinan, nifas, dan neonatus merupakan proses fisiologis yang berpotensi menimbulkan risiko bagi ibu dan bayi. Upaya optimal yang dapat dilakukan untuk menjaga keselamatan maternal dan neonatal adalah melalui penerapan Asuhan Kebidanan Komprehensif (Continuity of Care/ COC). Asuhan COC pada Ny. A bertujuan memberikan pelayanan kebidanan secara menyeluruh dan berkesinambungan pada masa kehamilan, persalinan, nifas, bayi baru lahir (BBL), dan keluarga berencana (KB) pada Ny. A G1P0A0. Penelitian ini menggunakan metode studi kasus dengan desain deskriptif. Subjek penelitian adalah ibu hamil Trimester II usia 29 minggu di wilayah Puskesmas Semowo. Pengumpulan data dilakukan melalui wawancara, observasi, pemeriksaan fisik, studi dokumentasi SOAP, serta telaah buku KIA, dengan pendekatan manajemen kebidanan Varney. Hasil asuhan menunjukkan bahwa selama kehamilan, Ny. A mengalami ketidaknyamanan Trimester II–III seperti cepat lelah dan gangguan tidur, sehingga diberikan edukasi tentang istirahat cukup, teknik relaksasi, nutrisi seimbang, dan tanda bahaya kehamilan. Proses persalinan berlangsung normal, dan bayi lahir sehat dengan antropometri sesuai usia gestasi, serta hasil skrining awal (SHK dan OAE) menunjukkan hasil normal. Pada masa nifas ditemukan keluhan puting lecet sehingga dilakukan edukasi perawatan payudara dan teknik menyusui yang benar. Pada kunjungan neonatus, bayi mengalami gangguan tidur sehingga diberikan intervensi pijat bayi (baby massage) untuk meningkatkan kualitas tidur dan bonding. Pada tahap KB, Ny. A memilih kontrasepsi implan setelah menerima konseling dan pemasangan telah dilakukan.